The main indicators analysis that characterize the food consumtion evolution in Romania in comparison between the period 2001-2006 and 2007-2014 - Raluca Necula; Mirela Stoian; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The analysis on the food consumption is particularly important because it helps us to discover information about the individual's health and economic differences between the two periods studied, outlining the economic impact on human food consumption and the worldwide food trends impact on the food transit that's going on within our country. It have been also noticed changes at the level of urban and rural areas and the differences between the two environments, which illustrates on the one hand the existence of changes in feeding with the accession to the European Union, the tendency being to decrease the number of calories, and the differences between environments demonstrating a higher food consumption for the countryside.
Keywords: 330; food consumption; calories; protein; carbohydrates; lipids